Biochar increases soil N2O emissions produced by nitrification-mediated pathways - Sánchez-García, María; Roig, Asunción; Sánchez-Monedero, Miguel A.; Cayuela, María L. (Frontiers in Environmental Science, 2014)
In spite of the numerous studies reporting a decrease in soil nitrous oxide (N2O) emissions after biochar amendment, there is still a lack of understanding of the processes involved. Hence the subject remains controversial, with a number of studies showing no changes or even an increase in N2O emissions after biochar soil application. Unraveling the exact causes of these changes, and in which circumstances biochar decreases or increases emissions, is vital to developing and applying successful mitigation strategies. With this objective, we studied two soils [Haplic Phaeozem (HP) and Haplic Calcisol (HC)], which showed opposed responses to biochar amendment. Under the same experimental conditions, the addition of biochar to soil HP decreased N2O emissions by 76%; whereas it increased emissions by 54% in soil HC. We combined microcosm experiments adding different nitrogen fertilizers, stable isotope techniques and the use of a nitrification inhibitor (dicyciandiamide) with the aim of improving our understanding of the mechanisms involved in the formation of N2O in these two soils. Evidence suggests that denitrification is the main pathway leading to N2O emissions in soil HP, and ammonia oxidation and nitrifier-denitrification being the major processes generating N2O in soil HC. Biochar systematically stimulated nitrification in soil HC, which was probably the cause of the increased N2O emissions. Here we demonstrate that the effectiveness of using biochar for reducing N2O emissions from a particular soil is linked to its dominant N2O formation pathway.